The Role of Tetra Hybrid Reinforcements on the Behavior of Aluminum Metal Matrix Composites. (8th September 2022) - Ashebir, Demeke Abay; Mengesha, Getinet Asrat; Sinha, Devendra Kumar
Abstract : Hybrid aluminum matrix composites (HAMCs) are a new class of advanced materials that can be customized and engineered to achieve specific properties for specific applications in specific environments. HAMCs find a wide range of popularity in the transportation sector because of lower noise and lower fuel consumption over other materials. This research aims to synthesize, characterize, and test the physicomechanical characteristics of tetra hybrid (SiC, Al2 O3, Gr, and sugarcane bagasse ash (SCBA)) reinforced HAMCs via powder metallurgy (PM) processing. Tetra hybrid reinforced HAMCs were synthesized using a pure Al matrix with fixed wt% of primary reinforcements (5 wt% SiC and 5 wt% Al2 O3 ) and varying wt% of secondary reinforcements such as 0.5, 2.5, 4.5, and 6.5 wt% Gr and 0.5, 2.5, 4.5, and 6.5 wt% SCBA. It mainly focused on phase purity investigation using XRD, thermal analysis using TGA-DTA, and surface area and micropore size analysis using BET and physicomechanical tests to explore the materials' behavior of the newly synthesized HAMCs. The increase in wt% of secondary reinforcements decreases both the density and porosity while increasing the hardness and compressive strength up to a certain level above which it begins to reverse because of the increase in wt% of hard particles of SiC, Al2 O3, and SCBA. The Vickers hardness and compressive strength of the AS4 HAMC with 10 wt% (SiC+Al2 O3 ) and 9 wt% (Gr+SCBA) were improved by 446.40% and 209.75%, respectively. The newly synthesized tetra hybrid reinforced HAMCs showed superior physicomechanical properties compared to pure Al and single and double reinforced HAMCs. As a result, the new tetra hybrid reinforced HAMC material is predicted to have potential applications in automotive, aerospace, defense, and various other structural applications.